BAI’ BITHAMAN AJIL, ALTERNATIF PEMBIAYAAN PERUMAHAN PADA PERBANKAN SYARIAH - Harahap, Lily Rahmawati (Fakultas Ekonomi Universitas IBA, 2017)
During this recent two decades, national economy sharia continiue growth.Though it just still smaller compare to the existing of conventional finance, itconscioused the growth of sharia finance currently has a significant enhancement. Thepositive and stable economy performance has given good opportunities to thedevelopment of sharia economy in Indonesia. The existence of syariah economy inIndonesia, who has a muslim mayority, is a new point of national economy history.Sharia banking is one of the tools for developing national economy sharia. Manyproducts offered by national sharia banking, which includes basic principles ofimplementation with profit sharing. One of them is Bai’ Bithaman Ajil, which is the partof trading (Baiah). Bai’ Bithaman Ajil product is expected as an alternative for society tochoose sharia banking as a mediator in transaction, specially to fulfill production needsas well as consumption needs, whose transactions are done on a long-term credit.